Antifungal activity of tannins isolated barks of Plumera rubra (Temple Flower) against the pathogenic fungus (Candida albicans). - Cejar, Kimby P.
The search for new sources of medicine which is highly beneficial to human health is needed to discover and produce more disease-preventing drugs and treatments as bacteria and fungi are increasing and becoming more resistant to present drugs. Tannins from the barks of Plumeria rubra (Temple Flower) were extracted with water and alcohol-ether mixture at 80 degrees centigrade Qualitative analysis (Gelatin Test, Acetic Acid-Lead Acetate Test, and Ferric Chloride Test) and Quantitative determination of tannin content were conducted. Quantitatively, 150 g barks of P. rubra has approximately 6.85 g of tannin (4.12 percent) and Qualitative tests gave positive results for all extract samples in determining the presence of tannins. Tannins gave white precipitates for Gelatin Test, yellow-brown precipitates for Aceti Acid-Lead Acetate Test, and greenish-black precipitates for Ferric Chloride Test. Candida albicans was selected as pathogenic fungus for the antifungal screening, cultured using Sabouraud Dextrose agar. 18-6mm discs were used and extracts were diluted to 5 percent, 15 percent, 25 percent, and 35 percent. Water was used as negative control and Ketoconazole (standard cream) was used as positive control. All tests were repeated thrice. Different concentrations of the extracts exhibited antifungal activity against C. albicans, with the highest zone of inhibition of 11.89 mm at 35 percent. Ketoconazole used as a positive control exhibited a zone of inhibition of 13.44 mm. This study proved that Plumeria rubra is one of the best sources of raw material for antifungal drug development due to the presence of tannin and other phytochemicals.